(NmETODIKA(B, (NTEHNIKA I REZULXTATY GEOFIZI^ESKOJ RAZWEDKI RUDNYH MESTOROVDENIJ (B:s [(NsBORNIK STATEJ(B] /s - (NbRODOWOJ(B, (NwLADIMIR wASILXEWI^s ((NeREWAN (B:s (NiZD(B-(NWO an aRMssr(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NzAGL(B. (NTAKVE(B: (NARM(B.s
(Nan aRMssr(B, (NiN(B-(NT GEOFIZIKI I INV(B. (NSEJSMOLOGIIs
Keywords: (NrUDNYE MESTOROVDENIQ (B- (NpOISKI I RAZWEDKA (B- (NsBORNIKIs